ANALISIS PROSEDUR PENGELOLAAN PENGADAAN BARANG (METODE PEMBAYARAN SPM-LS) DAN KEWAJIBAN PERPAJAKANNYA DI PENGADILAN TINGGI BANDUNG - Ali Al-ghifari, Luqman; Gunardi, Gunardi; Kesumah, Priatna; Fauzany, Riffka (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2025)
This scientific article focuses on the explanation of Analysis of Procurement Management Procedures and Tax Obligations at the Pengadilan Tinggi Bandung which aims to analyze its procurement system which has two payment methods, namely Surat Perintah Membayar-Langsung (SPM-LS) and to examine the management of income tax article 22 imposed on the procurement of goods by the government treasurer. The research method used is descriptive qualitative with data collection techniques through observation, interviews, documentation, and literature studies. The results of the study indicate that Pengadilan Tinggi Bandung has implemented procurement of goods and tax management quite well, but there are still obstacles in reporting the income tax article 22 Periodic Tax Returns caused by various things. The recommendations given include improving the integrated information system and consistency in tax reporting.